Senescence of immortal human fibroblasts by the introduction of normal human chromosome 6. - Sandhu, A K (1994)
In these studies we show that introduction of a normal human chromosome 6 or 6q can suppress the immortal phenotype of simian virus 40-transformed human fibroblasts (SV/HF). Normal human fibroblasts have a limited life span in culture. Immortal clones of SV/HF displayed nonrandom rearrangements in chromosome 6. Single human chromosomes present in mouse/human monochromosomal hybrids were introduced into SV/HF via microcell fusion and maintained by selection for a dominant selectable marker gpt, previously integrated into the human chromosome. Clones of SV/HF cells bearing chromosome 6 displayed limited potential for cell division and morphological characteristics of senescent cells. The loss of chromosome 6 from the suppressed clones correlated with the reappearance of immortal clones. Introduced chromosome 6 in the senescing cells was distinguished from those of parental cells by the analysis for DNA sequences specific for the donor chromosome. Our results further show that suppression of immortal phenotype in SV/HF is specific to chromosome 6. Introduction of individual human chromosomes 2, 8, or 19 did not impart cellular senescence in SV/HF. In addition, introduction of chromosome 6 into human glioblastoma cells did not lead to senescence. Based upon these results we propose that at least one of the genes (SEN6) for cellular senescence in human fibroblasts is present on the long arm of chromosome 6.